Analisis Kinerja Ekonomi Dan Pengelolaan Keuangan Daerah Provinsi Papua Barat - Rully Novie Wurarah; Siti Aisah Bauw (JFRES Journal of Fiscal and Regional Economy Studies, 2018)
The welfare of the people of West Papua who are depicted by macroeconomic conditions are still very far from the desired expectations. West Papua's HDI since the establishment of the Province has always been ranked at the bottom 2-3 of 32-34 provinces. The number of poor people although decreasing every year is still above the national average. On the other hand the development funds that have been used to build the economy in West Papua are quite large. From this description it needs to be questioned whether financial management has changed the economic performance of West Papua Province? The conclusion are 1) West Papua is more dominated by the oil and gas sector, mining which during this period experienced a decline in output, 2) the number of exports in the oil and gas sector and mining sector affecting employment in all sectors 3) Increased allocation of capital expenditure over the past 5 years is inconsistent and less giving encouragement to the creation of output in productive sectors, 4) Allocation of expenditure to the agricultural strategic sector is only 3 to 4.6 percent of expenditure allocation which results in stagnant middle and lower income, 5) Effectiveness of expenditure allocation less synchronous because spending allocations are dominated by government administration spending.